2012
DOI: 10.1002/eji.201142155
|View full text |Cite
|
Sign up to set email alerts
|

Unlike αβ T cells, γδ T cells, LTi cells and NKT cells do not require IRF4 for the production of IL‐17A and IL‐22

Abstract: [5,6] and, most recently, Th9 cells producing 8]. All of these subsets differentiate from common precursor cells depending on * These authors contributed equally to this work.C 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim www.eji-journal.eu 3190 Hartmann Raifer et al. Eur. J. Immunol. 2012. 42: 3189-3201 the subset-driving cytokines during the first contact with the respective antigen. In this regard, IL-12 and IL-4 are considered to be the most important cytokines for generating Th1 or Th2 cells, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 56 publications
3
35
1
1
Order By: Relevance
“…8B). Together with published findings on IRF4, also dispensable for IL-17 expression in gd27 2 cells (29,30), our data demonstrate that IL-17 production by gd27 2 cells, although dependent on the master transcription factor RORgt, does not rely on auxiliary transcriptional partners (BATF, RORa, IRF4) that promote CD4 Th17 cell differentiation.…”
Section: Th17 Transcription Factorssupporting
confidence: 88%
See 2 more Smart Citations
“…8B). Together with published findings on IRF4, also dispensable for IL-17 expression in gd27 2 cells (29,30), our data demonstrate that IL-17 production by gd27 2 cells, although dependent on the master transcription factor RORgt, does not rely on auxiliary transcriptional partners (BATF, RORa, IRF4) that promote CD4 Th17 cell differentiation.…”
Section: Th17 Transcription Factorssupporting
confidence: 88%
“…Consistent with this, IRF4 has been recently shown to be dispensable for the differentiation of IL-17-producing gd T cells (29,30). Although IRF4 and BATF cooperate in conventional CD4 T cells, it has been shown that BATF has a direct impact on IL-17 expression by innate-like iNKT cells (31), whereas IRF4 was not required (29). Therefore, building on these foundations, and on our previous identification of effector gd T cell subsets segregated on the basis of CD27 expression (10,(32)(33)(34), we have in this work assessed the specific roles of the transcription factors T-bet, Eomes, RORgt, BATF, and RORa in the production of IFN-g and IL-17 by gd T cells in vitro and in vivo.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…However, the efficiency of the CD4-driven Cre recombinase in ILCs was challenged (45). Nevertheless, differential requirements for the transcription factor IRF4 were recently reported between Th17 cells and ILC3s for the production of both IL-22 and IL-17 (46). Moreover, previous work demonstrated that IL-17 production in ILC3s can occur in both a STAT3-dependent and STAT3-independent manner (34).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Notch-Hes1 pathway and the noncanonical (RelB) NF-kB pathway as well as, in a gd thymocyte-extrinsic manner, NIK and RelA expression in the thymus are required for the generation of gdT17 cells (6)(7)(8). In contrast, IRF4, which is critically required for Th17 cell differentiation, is dispensable for the development of gdT17 cells (9). Although probably irrelevant for the de novo generation of gdT17 cells in the thymus, STAT3 is required for the expansion of gdT17 cells, and the selective expansion of gdT17 cells by IL-7 was reported to depend on STAT3 (10).…”
mentioning
confidence: 99%